The Impact of Smoking Sheesha on Gene Expression in Salivary Cells - Hoda, El-katerji (Université d'Ottawa / University of Ottawa, 2013)
Background: The health effects of sheesha smoking are not well addressed. Objective: To assess the association between sheesha tobacco smoking and gene expression pertinent to cancer. Methodology: Three linked studies were carried out: (1) investigation of gene expression in salivary cells before and after exposure to sheesha tobacco smoke in 15 participants; (2) a systematic review of the association between sheesha and cancer; and (3) a pilot survey to collect data on factors potentially relevant to the uptake and cessation of sheesha tobacco smoking. Results: In the short-term, sheesha smoking significantly reduced the expression of both xenobiotic metabolism genes and other genes known to have altered expression in tobacco related cancers in a range between 1.7 times and 55 times. The systematic review showed that sheesha may increase the risk of lung and esophageal cancers. The pilot survey identified misperceptions about safety, in line with other studies, an approach that could be used to investigate the characteristics of sheesha smokers on a larger scale, and specific issues to probe. Conclusion: High quality epidemiological evidence on long-term effects of sheesha smoking on cancer is lacking. However, sheesha smoking has short-term effects on the expression of genes known to be involved in tobacco-related cancers. This is of major concern given widespread misperceptions about the likely safety of sheesha tobacco smoking.
Keywords: sheesha; smoking; tobacco; gene expression; young adult